(untitled) (Global Journal of Management and Business Research, 2014)
Electronic commerce (online shopping) is increasing in popularity nowadays due to the popularity of computer usage and the prevalence of internet. Electronic commerce can produce numerous benefits to both sellers and consumers. Hence, the study of online consumer behavior can generate a better online atmosphere to facilitate greater profit to sellers and better online purchasing experience to consumer. Gender has universal characteristics, regardless of culture and time period. In this study, the gender differences in different aspects of online consumer behavior is concerned and investigated.